The Influence Of Home Environmental Factors On Patient Care With Chronic Obstructive Pulmonary Disease (COPD) - Adhyatma A; Yusraa, Yusraa; Sallo, Andi Kamal M.; Cahya, M. Robby Fajar; Idris, Baiq Nurainun Apriani; Rahmat, Rezqiqah Aulia (Jurnal EduHealth, 2024)
The influence of the home environment on the care of patients with chronic obstructive pulmonary disease (COPD) is an important factor in the management of this condition. The "Education and Training" method has proven effective in addressing this issue by improving COPD patients' understanding, skills and support in managing their home environment. Through comprehensive education, risk identification, development of home environment management skills, and use of appropriate health technologies, patients and their families can play an active role in creating a home environment that supports respiratory health. Support provided by the medical team and regular follow-up in providing education and training are important components in maintaining successful home environment management for COPD patients. Thus, the "Education and Training" approach not only helps to improve the quality of life of COPD patients, but can also reduce the risk of disease exacerbation and improve adherence to their treatment plan.